Stainless steel sheet for fuel cell separator

CN116635551BActive Publication Date: 2026-11-03JFE STEEL CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180084000.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-15
Filing Date
2021-12-13
Publication Date
2026-11-03
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

When existing stainless steel separators are used in fuel cells, they suffer from high contact resistance, poor durability, and difficulty in large-scale production. In particular, the use of hydrofluoric acid-containing treatment solutions leads to safety and stability issues.

Method used

Multiple etching methods are employed, including treating the stainless steel plate with an acidic aqueous solution of hydrogen peroxide and nitric acid to form a surface texture with sharp protrusions. Contact resistance is reduced by controlling the surface characteristic parameters Sa and Ssk, as well as controlling the ratio of [non-metallic form (Cr+Fe)] to [metallic form (Cr+Fe)]. Treatment with hydrofluoric acid is avoided.

Benefits of technology

This technology enables the safe production of stainless steel insulating components with low contact resistance, improving production efficiency and safety, reducing contact resistance, and making them suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116635551B_ABST
    Figure CN116635551B_ABST
Patent Text Reader

Abstract

The present invention provides a stainless steel sheet for fuel cell separators with low contact resistance, which can be extremely advantageously manufactured not only in terms of safety but also in terms of mass productivity. The parameter Sa specified in ISO 25178 is 0.15 μm to 0.50 μm, and the parameter Ssk specified in ISO 25178 is greater than 0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to stainless steel plates for fuel cell separators. Background Technology

[0002] In recent years, from the perspective of protecting the Earth's environment, the development of fuel cells with high power generation efficiency and no carbon dioxide emissions has been promoted. These fuel cells generate electricity through an electrochemical reaction of hydrogen and oxygen. The basic structure of a fuel cell is similar to a sandwich structure, consisting of an electrolyte membrane (ion exchange membrane), two electrodes (fuel electrode and air electrode), diffusion layers for O2 (air) and H2, and two separators (bipolar plates).

[0003] Furthermore, based on the type of electrolyte membrane used, they are classified into phosphoric acid fuel cells, fused carbonate fuel cells, solid oxide fuel cells, alkaline fuel cells, and solid polymer fuel cells (PEFC; proton-exchange membrane fuel cell or polymer electrolyte fuel cell), and their respective development is underway.

[0004] Among these fuel cells, solid polymer fuel cells, in particular, are expected to be used as power sources for electric vehicles, stationary generators for home or commercial use, and portable small generators.

[0005] Solid polymer fuel cells extract electricity from hydrogen and oxygen via a polymer membrane. Furthermore, in a solid polymer fuel cell, the membrane-electrode assembly (MEA) is sandwiched between a gas diffusion layer (such as carbon paper) and a separator, forming a single component (a so-called single cell unit). An electromotive force is then generated between the separator on the fuel electrode side and the separator on the air electrode side. It should be noted that the aforementioned membrane-electrode assembly is called a MEA, which is an integrated polymer membrane with an electrode material such as carbon black, on the inner and outer surfaces of the membrane, supported on a platinum-based catalyst. The thickness of the aforementioned MEA is tens to hundreds of μm. Additionally, the gas diffusion layer is usually integrated with the MEA.

[0006] Furthermore, when solid polymer fuel cells are used in practice, dozens to hundreds of individual cells as described above are typically connected in series to form a fuel cell. Here, the separator is required to (a) function not only as a partition separating the individual cells, but also to perform the following functions:

[0007] (b) A conductor that carries electrons generated during transport.

[0008] (c) The air flow path for supplying oxygen (air), and the hydrogen flow path for supplying hydrogen.

[0009] (d) The discharge path for removing the generated water and gas (which also serves as an air flow path and a hydrogen flow path),

[0010] Therefore, excellent durability and conductivity are required.

[0011] Durability is determined by corrosion resistance. This is because when the separator corrodes and metal ions dissolve, the proton conductivity of the polymer membrane (electrolyte membrane) decreases, thus reducing its power generation characteristics.

[0012] Furthermore, regarding electrical conductivity, it is preferable to have extremely low contact resistance between the separator and the gas diffusion layer. The reason for this is that if the contact resistance between the separator and the gas diffusion layer increases, the power generation efficiency of the solid polymer fuel cell decreases. In other words, the lower the contact resistance between the separator and the gas diffusion layer, the better the power generation characteristics.

[0013] To date, solid polymer fuel cells using graphite as the separator have been put into practical use. Graphite separators offer advantages such as low contact resistance and non-corrosion properties. However, graphite separators are susceptible to damage from impacts. Furthermore, graphite separators are difficult to miniaturize, and their processing for forming air and hydrogen flow paths is costly. These drawbacks of graphite separators have hindered the widespread adoption of solid polymer fuel cells.

[0014] Therefore, attempts were made to use metal blanks instead of graphite as blanks for the spacers. In particular, from the point of view of improving durability, various studies were conducted on the practical application of spacers using stainless steel, titanium, titanium alloys, etc. as blanks.

[0015] For example, Patent Document 1 discloses a technique using metals such as stainless steel and titanium alloys, which easily form passivation films, as insulating materials. However, in the technique disclosed in Patent Document 1, the formation of the passivation film leads to an increase in contact resistance. As a result, power generation efficiency decreases. Thus, the metal blank disclosed in Patent Document 1 has the problem of higher contact resistance compared to graphite blanks.

[0016] Therefore, in order to reduce the contact resistance, for example, Patent Document 2 discloses "a graphite-based stainless steel with excellent corrosion resistance and conductivity, characterized in that, by mass%, it contains C: 0.001-0.05%, Si: 0.001-0.5%, Mn: 0.001-1.0%, Al: 0.001-0.5%, N: 0.001-0.05%, Cr: 17-23%, Mo: less than 0.1%, the remainder being composed of Fe and unavoidable impurities, and having a film on its surface obtained by immersion in an immersion treatment solution, the immersion treatment solution being mainly composed of hydrofluoric acid or fluorinated nitric acid, and when the concentration of hydrofluoric acid is expressed as [HF] and the concentration of nitric acid is expressed as [HNO3], it has the relationship of: [HF]≧[HNO3]…[1]".

[0017] In addition, Patent Document 3 discloses "a stainless steel for a fuel cell separator, characterized in that the stainless steel containing more than 16 mass% Cr is subjected to electrolytic treatment and then subjected to immersion treatment in a fluorine-containing melt".

[0018] Furthermore, Patent Document 4 discloses "a stainless steel for a fuel cell separator, characterized in that, by mass percent, it contains, or is less than 0.03% C, less than 1.0% Si, less than 1.0% Mn, less than 0.01% S, less than 0.05% P, less than 0.20% Al, less than 0.03% N, 16-40% Cr, and at least one of the following: less than 20% Ni, less than 0.6% Cu, less than 2.5% Mo, with the remainder being stainless steel composed of Fe and unavoidable impurities."

[0019] When the surface of this stainless steel was measured by photoelectron spectroscopy, Fe was detected, and the ratio of (Cr+Fe) in the non-metallic form to (Cr+Fe) in the metallic form was ≥3.0.

[0020] In addition, Patent Document 5 discloses "a stainless steel for fuel cell separators with low surface contact resistance, comprising 16 to 40% by mass Cr, characterized in that the surface of the stainless steel has a region with a surface area ratio of more than 50% having a micro-uneven structure".

[0021] Existing technical documents

[0022] Patent documents

[0023] Patent Document 1: Japanese Patent Application Publication No. 8-180883

[0024] Patent Document 2: Patent No. 5768641

[0025] Patent Document 3: Japanese Patent Application Publication No. 2013-93299

[0026] Patent Document 4: Patent No. 5218612

[0027] Patent Document 5: International Publication No. 2013 / 080533

[0028] Patent Document 6: International Publication No. 2019 / 082591 Summary of the Invention

[0029] However, in manufacturing the stainless steel sheets disclosed in Patent Documents 2-5, if continuous immersion in a hydrofluoric acid-containing treatment solution is performed as an etching process, Fe ions and the like will dissolve from the steel sheet being treated. Due to this effect, the etching ability of hydrofluoric acid is reduced, and sometimes the desired reduction in contact resistance cannot be consistently achieved. Furthermore, because the hydrofluoric acid-containing treatment solution has extremely high chemical reactivity, safety issues arise during the processing. In addition, the disposal of the waste liquid discharged after the processing also raises safety concerns.

[0030] Therefore, the inventors conducted repeated research to solve the above problems. First, Patent Document 6 disclosed "a method for manufacturing a stainless steel plate for a fuel cell separator, which involves preparing a stainless steel plate as a blank, removing the oxide scale from the surface of the stainless steel plate, and then performing an electrolytic etching treatment on the activated area of ​​the stainless steel plate".

[0031] Using the technology described in Patent Document 6, even without using a treatment liquid containing hydrofluoric acid, it is possible to manufacture stainless steel plates for fuel cell separators with lower contact resistance in terms of safety and stability.

[0032] However, in the technology of the aforementioned Patent Document 6, the electrolytic etching process requires large-scale electrolytic equipment for mass production, resulting in significant equipment costs. Furthermore, performing electrolytic etching after stamping the stainless steel sheet presents complications due to the need to install electrodes on the stamped product.

[0033] The present invention was developed to solve the above-mentioned problems, and aims to provide a stainless steel plate for fuel cell separators with low contact resistance that can be manufactured with great advantages not only in terms of safety but also in terms of mass production.

[0034] In order to solve the above problems, the inventors conducted in-depth research and came to the following insights.

[0035] (1) First, from the viewpoint of improving mass production, the inventors performed various etching treatments on various stainless steel plates and measured the contact resistance of the treated stainless steel plates. Specifically, instead of the electrolytic etching treatment as in Patent Document 6, the stainless steel plates were immersed in various treatment solutions to perform etching treatment (hereinafter also referred to as the first immersion treatment), and the contact resistance of the treated stainless steel plates was measured.

[0036] (2) As a result,

[0037] • As the first impregnation treatment, an acidic aqueous solution containing hydrogen peroxide, copper ions, and halide ions was used as the treatment solution, and the treatment temperature and time were set to 30–50°C and 40–120 seconds, respectively, to carry out the impregnation treatment.

[0038] • After the first impregnation treatment, as a second impregnation treatment, any one of the following treatments (A) to (C) is performed, thereby finding that even without electrolytic etching treatment, a sufficient reduction in contact resistance can be obtained by etching treatment based on hydrofluoric acid.

[0039] (A) Immersion treatment using an acidic aqueous solution containing hydrogen peroxide, with the treatment temperature set at 30–60°C and the treatment time at 5–120 seconds.

[0040] (B) Immersion treatment using an aqueous solution containing nitric acid, with the treatment temperature set at 30–60°C and the treatment time at 5–120 seconds.

[0041] (C) Combine (A) and (B) above.

[0042] (3) Furthermore, the inventors used a laser microscope to confirm the surface characteristics of the stainless steel sheet (hereinafter also referred to as the stainless steel sheet of this application) after the above-mentioned impregnation treatment, and it can be seen that the following are formed on the surface of the stainless steel sheet of this application: Figure 1 The convex part shown has a sharp, concave-convex shape at its tip.

[0043] (4) Based on this, the inventors further conducted repeated research and discovered that by setting the parameter Sa specified in ISO 25178 to 0.15 μm to 0.50 μm, preferably 0.20 μm to 0.48 μm, and by setting the parameter Ssk specified in ISO 25178 to be greater than 0, a sufficient reduction in contact resistance can be achieved. Here, the parameter Sa specified in ISO 25178 is a surface roughness parameter, representing the arithmetic mean height. The arithmetic mean height is the average of the absolute values ​​of the height differences of each point relative to the average surface surface, and is a parameter commonly used when evaluating surface roughness. In addition, the parameter Ssk (skewness) specified in ISO 25178 is a surface roughness parameter, representing the symmetry of the height distribution. Figure 2As shown, when Ssk (skewness) is positive (greater than 0), the tip (upper end) of the convex part (peak) becomes sharper, while the tip (lower end) of the concave part (valley) becomes wider (approximately flat). On the other hand, when Ssk is negative (less than 0), the tip (upper end) of the convex part (peak) becomes wider (approximately flat), while the tip (lower end) of the concave part (valley) becomes sharper.

[0044] (5) Here, the inventors have considered the mechanism of the aforementioned contact resistance reduction effect as follows.

[0045] That is, the fuel cell separator comes into contact with a gas diffusion layer made of carbon paper, carbon cloth, etc., under a specified load. In stainless steel plates obtained through conventional electrolytic etching or hydrofluoric acid-based etching processes, numerous fine irregularities are formed on the steel plate surface. These fine irregularities increase the contact area between the separator (stainless steel plate) and the gas diffusion layer. As a result, the contact resistance decreases. On the other hand, as described above, the stainless steel plate in this application has irregularities with sharp-pointed protrusions on its surface. Therefore, as... Figure 3 As shown, when the spacer (stainless steel plate) comes into contact with the gas diffusion layer, the tip of the protrusion formed on the surface of the stainless steel plate of this application inserts into the carbon fibers of the gas diffusion layer. Furthermore, this portion (the portion where the tip of the protrusion inserts into the fibers of the gas diffusion layer) becomes an electrical pathway, thereby reducing contact resistance. In other words, the inventors believe that the mechanism by which the stainless steel plate of this application achieves a reduction in contact resistance differs from the mechanism by which contact resistance is reduced in stainless steel plates obtained through conventional electrolytic etching or hydrofluoric acid-based etching processes.

[0046] It should be noted that, in fact, when the inventors measured the surface characteristics of stainless steel plates obtained by conventional electrolytic etching and hydrofluoric acid-based etching processes, Sa was less than 0.15 μm and Ssk was a negative value (less than 0), which is significantly different from the surface characteristics of the stainless steel plate of this application.

[0047] (6) In addition, as a second impregnation treatment, performing (B) or (C) above, and controlling [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] to 8.0 or less, can further reduce the contact resistance.

[0048] Here, [non-metallic forms (Cr+Fe)] / [metallic forms (Cr+Fe)] refers to the ratio of the total amount of Cr and Fe existing in non-metallic forms on the surface of the steel plate to the total amount of Cr and Fe existing in metallic forms. Furthermore, [metallic forms (Cr+Fe)] and [non-metallic forms (Cr+Fe)] are the total atomic concentrations of Cr and Fe existing in metallic forms, and the total atomic concentrations of Cr and Fe existing in non-metallic forms, respectively, as determined by X-ray photoelectron spectroscopy.

[0049] (7) It should be noted that the inventors considered the above reasons as follows.

[0050] That is, as described above, the stainless steel sheet of this application has a protrusion with a sharp tip. Therefore, when the spacer (stainless steel sheet) comes into contact with the gas diffusion layer, the tip of the protrusion formed on the surface of the stainless steel sheet of this application inserts into the carbon fibers of the gas diffusion layer. Furthermore, this part (the part where the tip of the protrusion inserts into the fibers of the gas diffusion layer) becomes an electrical pathway, thereby reducing the contact resistance. However, during etching by the first immersion treatment, as the steel sheet dissolves, a large amount of contaminants (a mixture mainly composed of C, N, S, O, Fe, Cr, Ni, and Cu) are generated and adhere to the surface of the steel sheet. Since the resistance of the contaminants is high, the steel sheet that has just undergone the first immersion treatment (etching treatment) will have an increased contact resistance due to the influence of these contaminants. Based on this, as the second immersion treatment, the above-mentioned (B) or (C) is performed, that is, by using a treatment solution containing an aqueous nitric acid solution, which can particularly effectively remove the contaminants adhering to the surface of the steel sheet. Furthermore, the amount of contaminants on the steel plate surface is related to the ratio of [non-metallic (Cr+Fe)] to [metallic (Cr+Fe)]. It can be said that the lower the ratio of [non-metallic (Cr+Fe)] to [metallic (Cr+Fe)], the more effectively the contaminants can be removed. Therefore, by controlling the ratio of [non-metallic (Cr+Fe)] to below 8.0, the contact resistance can be further reduced.

[0051] (8) In addition, when investigating the effect of the average crystal grain size of the stainless steel plate on the dissolution behavior during the first immersion treatment, it was found that the average crystal grain size of the stainless steel plate is preferably 10 μm to 40 μm.

[0052] This invention is based on the above insights and was completed through further repeated research.

[0053] That is, the main components of the present invention are as follows.

[0054] 1. A stainless steel plate for use as a separator in a fuel cell, wherein the parameter Sa specified in ISO 25178 is 0.15 μm to 0.50 μm and the parameter Ssk specified in ISO 25178 is greater than 0.

[0055] 2. The stainless steel sheet for the fuel cell separator according to claim 1 above, wherein the parameter Sa specified in ISO 25178 is 0.20 μm to 0.48 μm.

[0056] 3. The stainless steel sheet for the fuel cell separator according to 1 or 2 above, wherein the ratio of [(Cr+Fe) other than metallic form] to [(Cr+Fe) metallic form] is 8.0 or less.

[0057] Here, [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] refers to the ratio of the total amount of Cr and Fe existing on the surface of the steel plate in non-metallic forms to the total amount of Cr and Fe existing in metallic forms.

[0058] 4. The stainless steel sheet for a fuel cell separator according to any one of claims 1 to 3 above, wherein it has the following composition by mass%: C: 0.100% or less, Si: 2.00% or less, Mn: 3.00% or less, P: 0.050% or less, S: 0.010% or less, Cr: 15.0 to 25.0%, Ni: 0.01 to 30.0%, Al: 0.500% or less, and N: 0.100% or less, with the remainder consisting of Fe and unavoidable impurities.

[0059] 5. The stainless steel plate for the fuel cell separator according to claim 4 above, wherein the composition further comprises one or more of the following: by mass %,

[0060] Cu: below 2.50%

[0061] Mo: below 4.00%, and

[0062] Elements selected from one or more of Ti, Nb and Zr: total less than 1.00%.

[0063] 6. The stainless steel plate for a fuel cell separator according to any one of claims 1 to 5, wherein the average crystal grain size is 10 μm to 40 μm.

[0064] According to the present invention, a stainless steel sheet for fuel cell separators with low contact resistance can be obtained, which is highly advantageous not only in terms of safety but also in terms of mass production. Attached Figure Description

[0065] [ Figure 1 [Image 1] is a photograph of the surface condition of a stainless steel plate (sample No. 6) used for a fuel cell separator according to an embodiment of the present invention, as observed using a laser microscope.

[0066] [ Figure 2 [Illustration] is a schematic diagram (cross-sectional view) showing the surface state when Ssk (skort) is positive (greater than 0) and negative (less than 0).

[0067] [ Figure 3 [ ] is a schematic diagram (cross-sectional view) showing the contact situation when a stainless steel plate (isolation member) for a fuel cell separator according to an embodiment of the present invention comes into contact with the carbon fiber of the gas diffusion layer. Detailed Implementation

[0068] (1) Stainless steel plate for fuel cell separator

[0069] The following describes a stainless steel sheet for a fuel cell separator according to one embodiment of the present invention. As described above, in the stainless steel sheet for a fuel cell separator according to one embodiment of the present invention, it is important to form an uneven structure with recesses and protrusions on the surface and to control the shape of the uneven structure.

[0070] The parameter Sa specified in ISO 25178 is 0.15 μm to 0.50 μm.

[0071] Sa is a surface roughness parameter specified in ISO 25178, representing the arithmetic mean height. The arithmetic mean height is the average of the absolute values ​​of the height differences between points relative to the average surface area, and is a parameter commonly used in evaluating surface roughness. As described above, in a fuel cell separator of one embodiment of the present invention, the stainless steel has a protrusion on its surface inserted into the carbon fibers of the gas diffusion layer when the separator (stainless steel plate) contacts the gas diffusion layer. This portion (where the protrusion tip is inserted into the gas diffusion layer fibers) becomes an electrical pathway, thereby reducing contact resistance. Therefore, in addition to the sharpness of the protrusion tip, it is also necessary for the protrusion tip to be fully inserted into the carbon fibers of the gas diffusion layer. Thus, Sa is 0.15 μm or more. Sa is preferably 0.20 μm or more. However, if Sa is greater than 0.50 μm, the thickness of the stainless steel plate becomes uneven due to the etching process. That is, etching occurs locally, resulting in thinning and easy breakage. Therefore, Sa is 0.50 μm or less. Sa is preferably 0.48 μm, more preferably 0.45 μm or less, and even more preferably 0.40 μm or less.

[0072] The parameter Ssk (skewness) specified in ISO 25178 is greater than 0.

[0073] The parameter Ssk (skear), specified in ISO 25178, is a surface roughness parameter that represents the symmetry of the height distribution. For example... Figure 2As shown, when Ssk (skex) is positive (greater than 0), the tip (upper end) of the convex portion (peak) becomes sharper, while the tip (lower end) of the concave portion (valley) becomes wider (approximately flat). On the other hand, when Ssk is negative (less than 0), the tip (upper end) of the convex portion (peak) becomes wider (approximately flat), while the tip (lower end) of the concave portion (valley) becomes sharper. As described above, in the stainless steel used for the fuel cell separator of one embodiment of the present invention, when the separator (stainless steel plate) contacts the gas diffusion layer, the tip of the convex portion formed on the surface of the stainless steel plate inserts into the carbon fiber of the gas diffusion layer. Furthermore, this part (the part where the tip of the convex portion inserts into the fiber of the gas diffusion layer) becomes an electrical path, thereby reducing the contact resistance. Therefore, the tip of the convex portion formed on the surface of the stainless steel plate needs to be sharp. Therefore, Ssk is greater than 0. Ssk is preferably 0.10 or higher. There is no particular upper limit to Ssk, but if it is excessively increased, the number of convex portions decreases, and sometimes the contact resistance is increased instead. Therefore, Ssk is preferably 1.0 or lower.

[0074] It should be noted that Sa and Ssk can be measured according to ISO 25178. For example, a laser microscope can be used as the measuring device. Furthermore, in the stainless steel plate for the fuel cell separator according to one embodiment of the present invention, it is sufficient that Sa is 0.15 μm to 0.50 μm and Ssk is greater than 0 on at least one side (the side in contact with the gas diffusion layer). It should be noted that steel plates manufactured by the etching process described later generally have Sa of 0.15 μm to 0.50 μm and Ssk greater than 0 on both sides.

[0075] [Other metallic forms (Cr+Fe)] / [Metallic forms (Cr+Fe)]: Below 8.0

[0076] As described above, by controlling the ratio of [non-metallic (Cr+Fe)] to [metallic (Cr+Fe)] to 8.0 or less, the effect of reducing contact resistance in the operating environment of the fuel cell separator can be further improved. Therefore, the ratio of [non-metallic (Cr+Fe)] to [metallic (Cr+Fe)] is preferably 8.0 or less. More preferably, it is 7.0 or less, further preferably 6.0 or less, and even more preferably 5.0 or less. It should be noted that if the ratio of [non-metallic (Cr+Fe)] to [metallic (Cr+Fe)] is greater than 8.0, it cannot be said that the stains on the steel plate surface are sufficiently removed, and the effect of further reducing contact resistance cannot be obtained. The lower limit of the ratio of [non-metallic (Cr+Fe)] to [metallic (Cr+Fe)] is not particularly limited, but if it is reduced excessively, the processing time becomes longer; therefore, the ratio of [non-metallic (Cr+Fe)] to [metallic (Cr+Fe)] is preferably 2.0 or more. It should be noted that the forms other than metals refer to oxides and hydroxides. Specifically, examples of Cr include CrO2, Cr2O3, CrOOH, Cr(OH)3, and CrO3. Examples of Fe include FeO, Fe3O4, Fe2O3, and FeOOH.

[0077] Here, [(Cr+Fe) outside the metallic form] / [(Cr+Fe) in the metallic form] is calculated as follows.

[0078] That is, X-ray photoelectron spectroscopy (hereinafter also known as XPS) is used to measure the surface of the steel plate. For the obtained Cr peak, the Cr peak existing in metallic form is separated from the Cr peak existing in non-metallic form. Similarly, for the obtained Fe peak, the Fe peak existing in metallic form is also separated from the Fe peak existing in non-metallic form. The sum of the atomic concentrations of Cr and Fe existing in non-metallic forms is divided by the sum of the atomic concentrations of Cr and Fe existing in metallic form to obtain [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)]. Specifically, a 10 mm square sample is cut from the steel plate, and the sample is measured using an X-ray photoelectron spectrometer (ULVAC-PHI X-tool) with an Al-Kα monochromatic X-ray source and a cutting angle of 45 degrees. Then, the measured Cr and Fe peaks are separated into peaks existing in metallic form and peaks existing in non-metallic form for Cr and Fe, respectively. Next, the sum of the atomic concentrations of Cr and Fe in their non-metallic forms, calculated thus, is divided by the sum of the atomic concentrations of Cr and Fe in their metallic forms, to obtain [non-metallic (Cr+Fe)] / [metallic (Cr+Fe)]. It should be noted that peak separation was performed using the Shirley method to remove the spectral background and employing the Gauss-Lorentz composite function (Lorentz function percentage: 30%).

[0079] In addition, the average crystal grain size of the stainless steel plate used for fuel cell separators in one embodiment of the present invention is preferably 10 μm to 40 μm.

[0080] Average crystal grain size: 10μm~40μm

[0081] Freshly rolled stainless steel sheet that has not undergone annealing has a uniform, non-recrystallized processing structure. If the first impregnation treatment (described later) is performed on such a freshly rolled sheet, uniform dissolution occurs within the stainless steel sheet. On the other hand, in stainless steel sheet that has undergone annealing (hereinafter also referred to as annealed stainless steel sheet), the boundaries between recrystallized grains (hereinafter also referred to as grain boundaries) become the starting point for dissolution. Therefore, if the first impregnation treatment (described later) is performed on such annealed stainless steel sheet, non-uniform dissolution occurs within the stainless steel sheet. In the case of non-uniform dissolution in the first impregnation treatment, compared to uniform dissolution, it is easier to create unevenness on the surface of the stainless steel sheet starting from a stage where less dissolution occurs.

[0082] Based on the above insights, the inventors have repeatedly studied the invention and discovered that by appropriately controlling the grain size of the stainless steel sheet, specifically by controlling the average crystal grain size within the range of 10 μm to 40 μm, the desired surface properties (Sa and Ssk) of the stainless steel sheet can be obtained with a smaller amount of solvent. If the amount of solvent can be reduced, numerous advantages can be achieved, such as shortening the processing time (immersion time) of the first immersion treatment, lowering the processing temperature, reducing the amount of treatment solution used, reducing the cost of treating used treatment solution, and increasing the product yield.

[0083] Here, if the average crystal grain size is 10 μm or more, sufficient defects accumulate at the grain boundaries, and the difference in solubility characteristics between the grain boundaries and the grains increases, thus appropriately achieving the aforementioned effect of reducing solubility. On the other hand, if the average crystal grain size is greater than 40 μm, the amount of grain boundaries per unit area decreases, and the aforementioned effect of reducing solubility is reduced. Therefore, the average crystal grain size of the stainless steel foil is preferably 10 μm to 40 μm.

[0084] In addition, the average crystal grain size of the stainless steel plate was determined based on EBSD (electron beam backscatter diffraction) analysis.

[0085] That is, a stainless steel sheet is embedded in resin and its surface is polished to expose a section parallel to the rolling direction of the stainless steel sheet. Next, EBSD analysis is performed, and the average crystal grain size is calculated based on the Area Fraction method. It should be noted that it is preferable to ensure that the field of view for EBSD analysis is 0.025 mm². 2 The above applies. For example, when using a stainless steel sheet with a thickness of 0.10 mm, the width of the field of view is preferably 0.25 mm or more. Other conditions can be determined using conventional methods. Furthermore, the grain size of each grain is determined by calculating the equivalent circle diameter based on the area of ​​each grain obtained using the Area Fraction method.

[0086] Furthermore, the stainless steel plate used for the fuel cell separator in one embodiment of the present invention is not particularly limited, but preferably contains, by mass percent, C: 0.100% or less, Si: 2.00% or less, Mn: 3.00% or less, P: 0.050% or less, S: 0.010% or less, Cr: 15.0 to 25.0%, Ni: 0.01 to 30.0%, Al: 0.500% or less, and N: 0.100% or less.

[0087] and may contain one or more of the following:

[0088] (a) Cu: less than 2.50%,

[0089] (b) Mo: less than 4.00%, and

[0090] (c) Elements selected from one or more of Ti, Nb, and Zr: totaling less than 1.00%,

[0091] The remaining portion consists of Fe and unavoidable impurities (hereinafter also referred to as the preferred composition).

[0092] The reasons are explained below. It should be noted that, unless otherwise stated, the "%" in the composition refers to the percentage by mass.

[0093] C: Below 0.100%

[0094] C reacts with Cr in the steel and precipitates as Cr carbides at the grain boundaries. Therefore, C leads to a decrease in corrosion resistance. From the viewpoint of corrosion resistance, the lower the C content, the better; the C content is preferably 0.100% or less. A more preferred C content is 0.060% or less. It should be noted that there is no particular limitation on the lower limit of the C content, but 0.001% is preferred.

[0095] Si: below 2.00%

[0096] Si is an effective deoxidizing element and is added during the steel smelting stage. Its effect is preferably achieved at a Si content of 0.01% or more. However, excessive Si content can lead to hardening and a decrease in ductility. Therefore, the Si content is preferably 2.00% or less, and more preferably 1.00% or less.

[0097] Mn: below 3.00%

[0098] Mn is an effective deoxidizing element and is added during the steel smelting stage. Its effect is preferably achieved at a Mn content of 0.01% or higher. However, if the Mn content exceeds 3.00%, corrosion resistance tends to decrease. Therefore, the Mn content is preferably 3.00% or less. More preferably, the Mn content is 1.50% or less, and even more preferably 1.00% or less.

[0099] P: below 0.050%

[0100] Polymer (P) reduces ductility, so its content should be as low as possible. However, if the P content is below 0.050%, a significant decrease in ductility does not occur. Therefore, the P content is preferably below 0.050%, and more preferably below 0.040%. There is no particular limitation on the lower limit of the P content, but excessive P removal leads to increased costs. Therefore, the P content is preferably above 0.010%.

[0101] S: below 0.010%

[0102] Sulfur (S) is an element that reduces corrosion resistance by combining with Mn to form MnS. However, if the S content is below 0.010%, a significant decrease in ductility does not occur. Therefore, the S content is preferably below 0.010%. There is no particular limitation on the lower limit of the S content, but excessive desulphurization leads to increased costs. Therefore, the S content is preferably above 0.001%.

[0103] Cr: 15.0–25.0%

[0104] To ensure corrosion resistance, the Cr content is preferably 15.0% or more. That is, if the Cr content is less than 15.0%, it is difficult to withstand long-term use as a fuel cell separator in terms of corrosion resistance. The Cr content is more preferably 18.0% or more. On the other hand, if the Cr content is greater than 25.0%, sufficient etching amount may not be obtained. Therefore, the Cr content is preferably 25.0% or less. The Cr content is more preferably 23.0% or less, and even more preferably 21.0% or less.

[0105] Ni: 0.01~30.0%

[0106] Ni is an effective element for improving the corrosion resistance of stainless steel. Furthermore, austenitic stainless steel and ferritic-austenitic duplex stainless steel typically contain a certain amount of Ni. However, if the Ni content exceeds 30.0%, hot workability decreases. Therefore, the Ni content is preferably 30.0% or less. More preferably, the Ni content is 20.0% or less. Additionally, the Ni content is preferably 0.01% or more.

[0107] It should be noted that the preferred lower limit for Ni content in austenitic stainless steel and ferritic-austenitic duplex stainless steel is 2.00%. Furthermore, when ferritic stainless steel contains Ni, the Ni content is preferably 2.00% or less, more preferably 1.00% or less. It should also be noted that the preferred lower limit for Ni content in ferritic stainless steel is 0.01%.

[0108] Al: below 0.500%

[0109] Al is an element used for deoxidation. Its effectiveness is preferably achieved at an Al content of 0.001% or more. However, if the Al content is greater than 0.500%, it sometimes leads to a decrease in ductility. Therefore, the Al content is preferably 0.500% or less. More preferably, the Al content is 0.010% or less, and even more preferably 0.005% or less.

[0110] N: below 0.100%

[0111] If the nitrogen content exceeds 0.100%, the formability decreases. Therefore, the nitrogen content is preferably 0.100% or less. More preferably, it is 0.050% or less, and even more preferably 0.030% or less. There is no particular limitation on the lower limit of the nitrogen content, but excessive nitrogen removal leads to increased costs. Therefore, the nitrogen content is preferably 0.002% or more.

[0112] In addition to the ingredients mentioned above, it may further contain the following ingredients.

[0113] Cu: below 2.50%

[0114] Cu is an effective element for promoting the formation of the austenite phase and improving the corrosion resistance of stainless steel. This effect is preferably achieved at a Cu content of 0.01% or higher. However, if the Cu content exceeds 2.50%, hot workability decreases, leading to a reduction in productivity. Therefore, when Cu is present, the Cu content is 2.50% or less. Preferably, the Cu content is 1.00% or less.

[0115] Mo: 4.00% or less

[0116] Mo is an effective element for inhibiting localized corrosion such as crevice corrosion in stainless steel. Its effectiveness is preferably achieved when the Mo content is 0.01% or higher. However, if the Mo content exceeds 4.00%, it leads to embrittlement of the stainless steel. Therefore, when Mo is present, the Mo content is 4.00% or less. The Mo content is preferably 2.50% or less.

[0117] Elements selected from one or more of Ti, Nb, and Zr: total less than 1.00%.

[0118] Ti, Nb, and Zr contribute to improved resistance to intergranular corrosion, and these elements can be contained individually or in combination. The effect is preferably achieved at a content of 0.01% or more for each element. However, when the total content of these elements exceeds 1.00%, ductility tends to decrease. Therefore, when containing Ti, Nb, and Zr, their total content is 1.00% or less. There is no particular lower limit to the total content of Ti, Nb, and Zr, but it is preferably 0.01% or more.

[0119] It should be noted that the components other than those mentioned above are Fe and unavoidable impurities.

[0120] Furthermore, the stainless steel plate used for the fuel cell separator in one embodiment of the present invention can be any of a ferritic stainless steel plate, an austenitic stainless steel plate, or a ferritic-austenitic duplex stainless steel plate. From a processability point of view, an austenitic stainless steel plate is preferred. Here, the microstructure of the ferritic stainless steel plate can be a single-phase microstructure of the ferrite phase, or it can contain precipitates of 1% or less by volume as the remainder other than the ferrite phase. The microstructure of the austenitic stainless steel plate can be a single-phase microstructure of the austenitic phase, or it can contain precipitates of 1% or less by volume as the remainder other than the austenitic phase. The microstructure of the ferritic-austenitic duplex stainless steel plate (hereinafter also referred to as duplex stainless steel plate) can be composed of a ferrite phase and an austenitic phase, or it can contain precipitates of 1% or less by volume as the remainder other than the ferrite phase and the austenitic phase. Examples of the precipitates include one or more selected from intermetallic compounds, carbides, nitrides, and sulfides. It should be noted that the determination of each phase can be carried out using conventional methods.

[0121] Furthermore, considering the mounting space and weight during fuel cell stacking, the thickness of the stainless steel plate used for the separator of the fuel cell in one embodiment of the present invention is preferably in the range of 0.03 to 0.30 mm. If the plate thickness is less than 0.03 mm, the production efficiency of the metal sheet decreases. On the other hand, if it is greater than 0.30 mm, the mounting space and weight during stacking increase. The thickness of the stainless steel plate used for the separator of the fuel cell in one embodiment of the present invention is more preferably 0.05 mm or more. Furthermore, the thickness of the stainless steel plate used for the separator of the fuel cell in one embodiment of the present invention is more preferably 0.15 mm or less.

[0122] (2) Manufacturing method of stainless steel plate for fuel cell separator

[0123] Next, a method for manufacturing an austenitic stainless steel plate for a fuel cell separator according to one embodiment of the present invention will be described.

[0124] [Preparation of stainless steel billet]

[0125] The preparation process is the process of preparing stainless steel sheets (hereinafter also referred to as billet stainless steel sheets) as raw materials. There are no particular limitations on the method of preparing billet stainless steel sheets; for example, billet stainless steel sheets with the above-mentioned composition can be prepared as follows.

[0126] That is, by hot-rolling a steel billet with the above-mentioned composition into a hot-rolled plate, hot-rolling annealing and pickling the hot-rolled plate as needed, then cold-rolling the hot-rolled plate into a cold-rolled plate of the desired thickness, and finally cold-rolling annealing the cold-rolled plate as needed, stainless steel plates with the above-mentioned composition can be prepared. It should be noted that the conditions for hot rolling, cold rolling, hot-rolled plate annealing, and cold-rolled plate annealing are not particularly limited and can be performed using conventional methods. Alternatively, pickling can be performed after cold-rolled plate annealing, followed by surface bright rolling. Furthermore, the cold-rolled plate can also be annealed to a bright annealing process.

[0127] Furthermore, from the viewpoint of controlling the average grain size of stainless steel sheets within a specified range, the final annealing conditions, i.e., finishing annealing, for cold-rolled sheets are particularly preferably controlled by appropriately regulating the finishing annealing temperature and time. For example, in austenitic stainless steel sheets, it is preferable to control the finishing annealing temperature in the range of 1050–1250°C and the finishing annealing time in the range of 20–90 seconds; in ferritic stainless steel sheets, it is preferable to control the finishing annealing temperature in the range of 750–1050°C and the finishing annealing time in the range of 20–90 seconds. Additionally, the finishing annealing atmosphere is preferably a non-oxidizing atmosphere (e.g., a mixture of H2 and N2 (volume ratio H2:N2 = 75:25, dew point: -50°C)).

[0128] [First immersion treatment (etching treatment)]

[0129] The prepared stainless steel sheet blank was subjected to an immersion treatment (etching treatment). As the first immersion treatment, an acidic aqueous solution containing hydrogen peroxide (0.1–5.0% by mass), copper ions (1.0–10.0% by mass), and halide ions (5.0–20.0% by mass), with a pH below 1.0, was used. The treatment temperature and time were 30–50°C and 40–120 seconds, respectively. By performing the etching treatment under these conditions, the amount of stainless steel dissolved was precisely controlled, thereby enabling the control of the shape of the uneven structure formed on the steel sheet surface as described above. The etching treatment conditions will be explained below. It should be noted that the amount of stainless steel dissolved during etching varies, particularly depending on the type of etching solution, temperature, and processing time. Therefore, it is important to properly control these conditions to obtain the desired surface properties (for example, because there are easily soluble and difficult-to-dissolve portions on the steel plate surface, etching creates unevenness on the surface. However, if the amount of stainless steel dissolved is too high, the difficult-to-dissolve portions on the steel plate surface will also be etched, the protrusions (peaks) will become flat, and Ssk will become negative). First, the preferred concentrations of each component contained in the aforementioned etching solution will be explained.

[0130] Hydrogen peroxide: 0.1–5.0% by mass

[0131] If the concentration of hydrogen peroxide is less than 0.1% by mass, the ability to remove copper-containing products precipitated on the steel plate surface decreases, making continuous etching impossible. On the other hand, if the concentration of hydrogen peroxide is greater than 5.0% by mass, the effect saturates. Therefore, the concentration of hydrogen peroxide is preferably 0.1% to 5.0% by mass.

[0132] Copper ions: 1.0–10.0% by mass

[0133] If the concentration of copper ions is less than 1.0% by mass, the etching ability is reduced, and the desired uneven structure cannot be formed on the steel plate surface. On the other hand, if the concentration of copper ions is greater than 10.0% by mass, more deposits adhere to the steel plate surface, and even a second immersion treatment in the next process cannot adequately remove the stains. Therefore, the concentration of copper ions is preferably 1.0 to 10.0% by mass. The concentration of copper ions is preferably 2.0% by mass or more, and more preferably 5.0% by mass or more.

[0134] Halide ions: 5.0–20.0% by mass

[0135] If the concentration of halide ions is less than 5.0% by mass, the passivation film on the surface of the stainless steel plate cannot be sufficiently destroyed, and etching cannot proceed adequately. On the other hand, if the concentration of halide ions is greater than 20.0% by mass, local pitting corrosion is accelerated, potentially creating holes in the steel plate. Therefore, the concentration of halide ions is preferably 5.0 to 20.0% by mass. The concentration of halide ions is preferably 10.0% by mass or more. Furthermore, the concentration of halide ions is preferably 15.0% by mass or less. There is no particular limitation on the type of halide ion source; for example, hydrogen halides or alkali metal halides are preferred, and hydrochloric acid or sodium chloride are more preferred.

[0136] pH: below 1.0

[0137] If the pH of the treatment solution is greater than 1.0, the required uneven texture cannot be formed on the steel plate surface due to reduced etching ability. Therefore, the pH of the treatment solution is kept below 1.0. It should be noted that the pH of the treatment solution is preferably lower, more preferably below 0.1.

[0138] The above aqueous solution can be prepared by stirring an aqueous hydrogen peroxide solution, a copper compound that provides copper ions, a halide that provides halide ions, and water until homogeneous.

[0139] Processing temperature (temperature of the processing solution): 30~50℃

[0140] If the processing temperature is below 30°C, the etching ability decreases and the processing time increases. On the other hand, if the processing temperature is above 50°C, the stability of the processing solution decreases. Therefore, the processing temperature is set between 30°C and 50°C.

[0141] Processing time (immersion time): 40–120 seconds

[0142] If the processing time is less than 40 seconds, sufficient etching amount cannot be obtained. On the other hand, if the processing time is greater than 120 seconds, the required uneven structure cannot be formed on the steel plate surface. Furthermore, productivity decreases. Therefore, the processing time is set to 40 to 120 seconds. It should be noted that the etching amount varies depending on the type of stainless steel. Depending on the type of steel, the processing time is more preferably adjusted within the range of 40 to 120 seconds.

[0143] There are no special limitations other than those mentioned above. Conventional methods are acceptable. It should be noted that while the above description describes immersing the stainless steel billet in an aqueous solution used as the treatment liquid, any contact between the stainless steel billet and the aqueous solution, such as dripping or spraying the solution, is also acceptable. In this case, the treatment time is the contact time between the stainless steel billet and the aqueous solution.

[0144] [Second impregnation treatment (stain removal treatment)]

[0145] Following the first impregnation treatment described above, the stainless steel billet is further subjected to a second impregnation treatment.

[0146] (A) Immersion treatment using an acidic aqueous solution containing hydrogen peroxide, with treatment temperatures and times ranging from 30 to 60°C and 5 to 120 seconds respectively.

[0147] (B) Immersion treatment using an aqueous solution containing nitric acid at a temperature of 30–60°C and a treatment time of 5–120 seconds, or

[0148] (C) Perform a combination of the above (A) and (B) processes. In this way, the stains formed during the first immersion process (etching process) can be dissolved (removed).

[0149] That is, after the first impregnation treatment, a high-resistivity mixture (mainly composed of C, N, S, O, Fe, Cr, Ni, and Cu) is formed on the surface of the stainless steel plate. If these residues remain, even if the desired uneven structure is obtained, they can sometimes cause an increase in contact resistance. Based on this, after the first impregnation treatment, an impregnation treatment is performed in an acidic aqueous solution containing hydrogen peroxide or a solution containing nitric acid to remove the aforementioned stains and achieve the effect of reducing contact resistance.

[0150] Here, an example of an acidic aqueous solution containing hydrogen peroxide is a mixture of hydrogen peroxide and sulfuric acid. Similarly, an example of a solution containing nitric acid is an aqueous solution of nitric acid.

[0151] Furthermore, when using a mixed aqueous solution of hydrogen peroxide and sulfuric acid, the concentration of hydrogen peroxide is preferably 0.5 to 10.0% by mass, and the concentration of sulfuric acid is preferably 1.0 to 10.0% by mass. Further, when using an aqueous solution of nitric acid, the concentration of nitric acid is preferably 1.0 to 40.0% by mass. It should be noted that in the mixed aqueous solution of hydrogen peroxide and sulfuric acid, the components other than hydrogen peroxide and sulfuric acid, and in the aqueous solution of nitric acid, the components other than nitric acid, are essentially water.

[0152] Furthermore, in any of the cases (A) to (C) above, the processing temperature (temperature of the processing liquid) of the second impregnation treatment is preferably 30 to 60°C.

[0153] Furthermore, a longer processing time (immersion time) promotes stain removal, but if it is too long, the effect becomes saturated, reducing productivity. Therefore, in any of the cases (A) to (C) above, the processing time is preferably 5 to 120 seconds. A processing time of 30 seconds or more is more preferred. A processing time of 90 seconds or less is even more preferred.

[0154] In addition, as described in (B) or (C) above, by using an aqueous solution containing nitric acid for immersion treatment, the stains formed during the first immersion treatment (etching treatment) can be dissolved (removed) more effectively, and the effect of reducing contact resistance can be further improved.

[0155] It should be noted that during the second immersion treatment, wiping the surface of the stainless steel sheet being treated with a non-woven cloth or similar material as needed facilitates the removal of stains, thereby ensuring a more stable and further reduction in contact resistance. Furthermore, while the above description mentions immersing the stainless steel sheet blank in an aqueous solution used as the treatment liquid, any contact between the stainless steel sheet blank and the aqueous solution, such as dripping or spraying, is also acceptable. In this case, the treatment time is the contact time between the stainless steel sheet blank and the aqueous solution. Additionally, besides continuous treatment of the steel strip, the second immersion treatment can also be performed after the strip has been shaped into a separator.

[0156] ·other

[0157] After the first impregnation treatment or the second impregnation treatment described above, a surface treatment film can be further formed on the surface of the steel plate. The formed surface treatment film is not particularly limited, but preferably uses a material with excellent corrosion resistance and conductivity in the operating environment of the fuel cell separator. Examples of preferred materials include metal layers, alloy layers, metal oxide layers, metal carbide layers, metal nitride layers, carbon material layers, conductive polymer layers, organic resin layers containing conductive substances, or mixtures thereof.

[0158] Examples of metal layers include Au, Ag, Cu, Pt, Pd, W, Sn, Ti, Al, Zr, Nb, Ta, Ru, Ir, and Ni, with Au and Pt being preferred.

[0159] In addition, examples of alloy layers include Sn alloy layers such as Ni-Sn (Ni3Sn2, Ni3Sn4), Cu-Sn (Cu3Sn, Cu6Sn5), Fe-Sn (FeSn, FeSn2), Sn-Ag, Sn-Co, Ni-W, Ni-Cr, Ti-Ta, etc., with Ni-Sn and Fe-Sn alloy layers being preferred.

[0160] Furthermore, examples of metal oxide layers include SnO2, ZrO2, TiO2, WO3, SiO2, Al2O3, Nb2O5, IrO2, RuO2, PdO2, Ta2O5, Mo2O5, and Cr2O3, among which TiO2 and SnO2 are preferred.

[0161] In addition, examples of metal nitride layers and metal carbide layers include TiN, CrN, TiCN, TiAlN, AlCrN, TiC, WC, SiC, B4C, molybdenum nitride, CrC, TaC, and ZrN, among which metal nitride layers of TiN are preferred.

[0162] In addition, carbon material layers such as graphite, amorphous carbon, diamond-like carbon, carbon black, fullerene, and carbon nanotubes can be cited as examples, with graphite or diamond-like carbon being the preferred carbon material layers.

[0163] Furthermore, examples of conductive polymer layers include polyaniline and polypyrrole.

[0164] Furthermore, the organic resin layer containing a conductive substance contains at least one conductive substance selected from the metal, alloy, metal oxide, metal nitride, metal carbide, carbon material, and conductive polymer layers constituting the aforementioned metal layer, alloy layer, metal oxide layer, metal nitride, metal carbide, carbon material, and conductive polymer. It also contains at least one organic resin selected from epoxy resin, phenolic resin, polyamide-imide resin, polyester resin, polyphenylene sulfide resin, polyamide resin, polyurethane resin, acrylic resin, polyethylene resin, polypropylene resin, carbodiimide resin, and phenolic epoxy resin. For example, phenolic resin with dispersed graphite and epoxy resin with dispersed carbon black are preferred as such organic resin layers.

[0165] It should be noted that metals and carbon materials (especially graphite and carbon black) are preferred as the aforementioned conductive materials. Furthermore, the content of the conductive material is not particularly limited, as long as the conductivity specified in the separator for solid polymer fuel cells is achieved.

[0166] In addition, as the aforementioned mixture layer, examples include mixture layers such as Ni-Sn alloys with TiN dispersion.

[0167] The above treatment can also be performed after the stainless steel sheet is processed into the shape of the separator.

[0168] Example

[0169] Example 1

[0170] Prepare stainless steel sheet blanks with a thickness of 0.10 mm and a composition of steel No. A to G as listed in Table 1 (the remainder being Fe and unavoidable impurities). Then, subject the prepared stainless steel sheet to a first immersion treatment (etching treatment) and a second immersion treatment (stain removal treatment) according to the conditions shown in Tables 2 and 3 to obtain a stainless steel sheet for fuel cell separators. It should be noted that, in the above treatments, after the second immersion treatment, the stainless steel sheet is immersed in pure water to stop the reaction.

[0171] Etching solution A1

[0172] Hydrogen peroxide: 0.2% by mass

[0173] Copper ions: 1.5% by mass

[0174] Chloride ions: 10.0% by mass

[0175] Remaining portion: water

[0176] pH: 0.05

[0177] It should be noted that the copper ions and chloride ions originate from copper sulfate pentahydrate and hydrochloric acid, respectively.

[0178] Etching solution A2

[0179] Hydrogen peroxide: 0.3% by mass

[0180] Copper ions: 2.0% by mass

[0181] Chloride ions: 15.0% by mass

[0182] Remaining portion: water

[0183] pH: 0.05

[0184] It should be noted that the copper ions and chloride ions originate from copper sulfate pentahydrate and hydrochloric acid, respectively.

[0185] Etching solution A3

[0186] Hydrogen peroxide: 0.3% by mass

[0187] Copper ions: 9.0% by mass

[0188] Chloride ions: 10.0% by mass

[0189] Remaining portion: water

[0190] pH: 0.05

[0191] It should be noted that the copper ions and chloride ions originate from copper sulfate pentahydrate and hydrochloric acid, respectively.

[0192] • Etching treatment A4

[0193] Hydrogen peroxide: 2.0% by mass

[0194] Copper ions: 2.0% by mass

[0195] Chloride ions: 10.0% by mass

[0196] Remaining portion: water

[0197] pH: 0.05

[0198] It should be noted that the copper ions and chloride ions originate from copper sulfate pentahydrate and hydrochloric acid, respectively.

[0199] • Stain Removal Solution B1

[0200] Hydrogen peroxide: 3.0% by mass

[0201] Sulfuric acid: 6.0% by mass

[0202] Remaining portion: water

[0203] • Stain Removal Solution B2

[0204] Hydrogen peroxide: 2.0% by mass

[0205] Sulfuric acid: 4.0% by mass

[0206] Remaining portion: water

[0207] • Stain Removal Solution N1

[0208] Nitric acid: 30% by mass

[0209] Remaining portion: water

[0210] For the stainless steel plate used in the fuel cell separator obtained in this way, Sa and Ssk were measured according to ISO 25178. It should be noted that a laser microscope (Keyence VK-X250 / X260) was used for the measurement. Specifically, a sample was removed from the stainless steel plate used in the fuel cell separator, and the surface shape data of a 50μm × 50μm area on both sides of the sample were measured using the aforementioned laser microscope with a 150x objective lens. The obtained data was analyzed using the analysis software "Multi-file Analysis Application" provided with the device, and Sa and Ssk were calculated for both sides of the sample. It should be noted that before analyzing Sa and Ssk, image processing was performed to remove portions of light intensity outside the threshold range (0.00–99.5) and interpolate, followed by smoothing using a Gaussian function and noise removal by setting segmentation levels. Then, a reference plane was set to be used as the measurement reference plane, and the surface was corrected to a plane using quadratic surface correction. Furthermore, a Gaussian S-filter with a specified cutoff wavelength of 0.5μm was used. The test results are shown in Tables 2 and 3. It should be noted that since the values ​​of Sa and Ssk are almost identical on both sides of any specimen, the values ​​of Sa and Ssk measured on one side of the specimen are used as representative values ​​in Tables 2 and 3. Additionally, for reference, for stainless steel plates of steel No. B in Table 1 used as billets, 10% by mass sulfuric acid was used at -1 mA / cm². 2 ×90 seconds, and +0.03mA / cm 2 Electrolytic treatment was carried out under conditions of ×90 seconds, and the Sa and Ssk values ​​of the treated steel plate were measured. Sa was 0.14 μm and Ssk was 0.90.

[0211] Furthermore, for samples No. 13 to 21, the ratio of [non-metallic form (Cr+Fe)] to [metallic form (Cr+Fe)] was calculated using the method described above. The results are also recorded in Table 3. It should be noted that the composition of the stainless steel plate used for the fuel cell separator is substantially the same as that of each steel No. recorded in Table 1, satisfying any of the above-mentioned preferred composition ranges.

[0212] In addition, the contact resistance was evaluated using the stainless steel plate obtained for the fuel cell separator according to the following points.

[0213] • Evaluation of contact resistance

[0214] A specified sample is cut from the stainless steel sheet used for the fuel cell separator obtained as described above. Next, the sample is sandwiched between carbon paper (Toray Corporation TGP-H-120), and copper plates are brought into contact with gold-plated electrodes from both sides, applying a pressure of 0.98 MPa (=10 kg / cm²) per unit area. 2 The pressure is used to guide the flow of current. Then, the voltage difference between the electrodes is measured, and the resistance is calculated. This measured resistance value is then multiplied by the area of ​​the contact surface, divided by 2, and the internal resistance of the carbon paper (3 mΩ·cm) is subtracted from this value. 2 The value of ) is used as the contact resistance value ([contact resistance value (mΩ·cm) 2 )]={[Measured value of electrical resistance (mΩ)]×[Contact area (cm²)] 2 ()]÷2}-3), evaluate the contact resistance according to the following criteria. The evaluation results are recorded in Tables 2 and 3.

[0215] ◎(Qualified (Exceptionally Excellent)): 5mΩ·cm 2 the following

[0216] ○ (Qualified): Greater than 5mΩ·cm 2 And 10mΩ·cm 2 the following

[0217] × (Unacceptable): Greater than 10 mΩ·cm 2

[0218] • Evaluation of corrosion resistance (stability of the insulating component in the operating environment)

[0219] A specified sample was cut from the stainless steel sheet used for the fuel cell separator obtained as described above. Next, the sample was immersed in an aqueous sulfuric acid solution containing 0.1 ppm hydrofluoric acid, pH 3.0, at 80°C. Then, simulating the separator's operating environment, the sample was kept in the sulfuric acid solution at a potential of 0.6V for 25 hours, and the current density value after 25 hours was measured. It should be noted that Ag / AgCl (saturated KCl) was used as the reference electrode. Then, based on the measured current density value after 25 hours, the corrosion resistance (stability of the separator in the operating environment) after 25 hours was evaluated according to the following criteria. The evaluation results are recorded in Tables 2 and 3.

[0220] ○ (Pass): 1μA / cm 2 the following

[0221] × (Unacceptable): Greater than 1 μA / cm 2

[0222]

[0223]

[0224]

[0225] The following can be clarified based on Tables 2 and 3.

[0226] (a) In all the invention examples, the desired low contact resistance was achieved. Good corrosion resistance (stability of the insulating component in the operating environment) was also obtained.

[0227] (b) As a second impregnation treatment, in the invention example using an aqueous solution containing nitric acid, a particularly low contact resistance was obtained.

[0228] (c) On the other hand, the desired low contact resistance was not obtained in any of the comparative examples.

[0229] Example 2

[0230] For steel symbols B and H in Table 1, cold-rolled stainless steel sheets with a thickness of 0.10 mm were prepared. In addition, for a portion of the stainless steel sheets, after cold rolling, they were further finished and annealed in a mixed atmosphere of H2 and N2 (volume ratio H2:N2 = 75:25, dew point: -50℃) under the conditions shown in Table 4.

[0231] Next, after measuring the thickness of these stainless steel blanks using a micrometer, the first immersion treatment (etching treatment) and the second immersion treatment (stain removal treatment) were performed according to the conditions shown in Table 4 to obtain stainless steel sheets for fuel cell separators. It should be noted that the treatment solutions A1 and N1 in Table 4 are the same as those used in Example 1. It should also be noted that in the above treatments, after the second immersion treatment, the stainless steel sheets were immersed in pure water to stop the reaction.

[0232] The thickness of the stainless steel sheet for fuel cell separators thus obtained was measured using a micrometer. The thickness reduction caused by the impregnation treatment was calculated by subtracting the thickness of the stainless steel sheet for fuel cell separators after the impregnation treatment from the thickness of the stainless steel sheet blank measured before the impregnation treatment. Additionally, Sa and Ssk were measured according to the same criteria as in Example 1. Furthermore, the average grain size was measured according to the above criteria. The measurement results are recorded in Table 4. "Cannot be measured" in the average grain size column of Table 4 means that grain boundaries could not be observed in EBSD (electron beam backscatter diffraction) analysis, and therefore the average grain size could not be measured. Additionally, [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] was calculated according to the same criteria as in Example 1. The results are also recorded in Table 4. It should be noted that the composition of the stainless steel sheet for fuel cell separators obtained in the end is substantially the same as the composition of each steel No. listed in Table 1, satisfying any of the above-mentioned preferred composition ranges.

[0233] In addition, following the same points as in Example 1, the stainless steel plate used for the above-mentioned fuel cell separator was evaluated for (1) contact resistance and (2) corrosion resistance. The evaluation results are recorded in Table 4.

[0234]

[0235] As shown in Table 4, the desired low contact resistance was achieved in all the invention examples. Good corrosion resistance was also obtained.

[0236] Among them, samples No. 2-3, 2-4, 2-7 and 2-8 with an average crystal grain size of 10μm to 40μm all showed a reduction in the amount of stainless steel plate dissolved during the first impregnation treatment and obtained particularly low contact resistance.

Claims

1. A stainless steel plate for use as a separator in a fuel cell, comprising the following components: By mass%, C: less than 0.100%, Si: less than 2.00%, Mn: less than 3.00%, P: less than 0.050%, S: less than 0.010%, Cr: 15.0–25.0%, Ni: 0.01–30.0%, Al: less than 0.500%, and N: less than 0.100%, with the remainder consisting of Fe and unavoidable impurities. The parameter Sa specified in ISO 25178 is 0.15 μm to 0.50 μm, and the parameter Ssk specified in ISO 25178 is greater than 0. Furthermore, the average crystal grain size of the stainless steel plate is 10μm to 40μm.

2. The stainless steel plate for the fuel cell separator according to claim 1, wherein, The parameter Sa specified in ISO 25178 is 0.20 μm to 0.48 μm.

3. The stainless steel plate for the fuel cell separator according to claim 1, wherein, [Other forms (Cr+Fe)] / [Metallic forms (Cr+Fe)] is 8.0 or less. Wherein, [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] refers to the ratio of the total atomic concentration of Cr and Fe existing in non-metallic forms on the surface of the steel plate to the total atomic concentration of Cr and Fe existing in metallic forms.

4. The stainless steel plate for the fuel cell separator according to claim 2, wherein, [Other forms (Cr+Fe)] / [Metallic forms (Cr+Fe)] is 8.0 or less. Wherein, [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] refers to the ratio of the total atomic concentration of Cr and Fe existing in non-metallic forms on the surface of the steel plate to the total atomic concentration of Cr and Fe existing in metallic forms.

5. The stainless steel plate for a fuel cell separator according to any one of claims 1 to 4, wherein, The composition further contains, by mass%, one or more of the following: Cu: below 2.50% Mo: below 4.00%, and Elements selected from one or more of Ti, Nb and Zr: total less than 1.00%.

Citation Information

Patent Citations

  • Solid polymer electrolytic fuel cell

    JP1996180883A

  • Method for manufacturing stainless steel for fuel battery separators, stainless steel for fuel battery separators, fuel battery separator, and fuel battery

    JP2013093299A

  • Stainless steel for fuel-cell separators

    WO2013080533A1

  • Method for producing stainless steel plate for fuel cell separator

    WO2019082591A1

  • Titanium material or titanium alloy material used for fuel cell separator excellent in contact conductivity to carbon and durability, fuel cell separator using same, and fuel cell

    CN104981931A